2004
DOI: 10.1016/j.neurobiolaging.2003.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The microglial phagocytic role with specific plaque types in the Alzheimer disease brain

Abstract: Alzheimer disease (AD) involves glial inflammation associated with amyloid plaques. The role of the microglial cells in the AD brain is controversial, as it remains unclear if the microglia form the amyloid fibrils of plaques or react to them in a macrophage-phagocytic role. Also, it is not known why microglia are preferentially associated with some amyloid plaque types. This review will provide substantial evidence to support the phagocytic role of microglia in the brain as well as explain why microglia are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
131
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 69 publications
10
131
0
1
Order By: Relevance
“…Because a significant amyloid load is already present at the time of earliest clinical symptoms (Lopresti et al, 2005), a therapeutic approach that addresses the deleterious effects of existing amyloid deposits is essential (Schenk, 2002). Although the production of ␤-amyloid (A␤), the fibrillary component of amyloid plaques, is thought to be primarily neuronal (Goedert, 1987;Calhoun et al, 1999), it is the microglial cells that react to amyloid as to other brain injuries, and microglia have been shown to have the ability to phagocytose A␤, at least in culture (Bard et al, 2000;Rogers et al, 2002;D'Andrea et al, 2004;Frackowiak et al, 2005). Indeed, the most successful of the amyloid clearing therapies, immunization, has been indirectly linked to microglial activation (Hardy and Selkoe, 2002;Wilcock et al, 2004;Barger, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Because a significant amyloid load is already present at the time of earliest clinical symptoms (Lopresti et al, 2005), a therapeutic approach that addresses the deleterious effects of existing amyloid deposits is essential (Schenk, 2002). Although the production of ␤-amyloid (A␤), the fibrillary component of amyloid plaques, is thought to be primarily neuronal (Goedert, 1987;Calhoun et al, 1999), it is the microglial cells that react to amyloid as to other brain injuries, and microglia have been shown to have the ability to phagocytose A␤, at least in culture (Bard et al, 2000;Rogers et al, 2002;D'Andrea et al, 2004;Frackowiak et al, 2005). Indeed, the most successful of the amyloid clearing therapies, immunization, has been indirectly linked to microglial activation (Hardy and Selkoe, 2002;Wilcock et al, 2004;Barger, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the AD brain, activated microglia are found in the direct vicinity of Aβ plaques (D'Andrea et al, 2004;Itagaki et al, 1989). Initially, they take on a neuroprotective role by releasing amyloid-degrading enzymes for the clearance of amyloid fibrils in the early stages of the disease.…”
Section: Supplementary Introductionmentioning
confidence: 99%
“…We have shown that blood-borne monocyte/ macrophages of AD patients migrate across the blood-brain barrier into AD brain but are defective in clearance of A␤ in neuritic plaques (4), and they overexpress cyclooxygenase-2 and inducible NO synthase (4). Resident microglia in AD brain display markers of inflammation (5,6), phagocytosis (7), and proinflammatory but not prophagocytic genes (8). However, most microglia invading A␤ plaques in transgenic mouse models are bone marrow-derived, not resident microglia (9).…”
mentioning
confidence: 99%